Different cytokine patterns associate with melancholia severity among inpatients with major depressive disorder - Alves, Lucas Primo de Carvalho (2022)
Background: Six melancholic features (MFs) of the Hamilton Depression Rating Scale (HAM-D6) represent the construct of melancholia along a continuum of severity (from least to most severe: depressed mood, work and activities, somatic symptoms, psychic anxiety, guilty feelings, psychomotor retardation). We aimed to evaluate the association between these MFs and inflammatory cytokines (IC) in the blood. Methods: Each IC [interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), interleukin 2 (IL-2), IL-4, IL-6, IL-10, and IL-17] was associated with the HAM-D6 MFs of 139 severely depressed inpatients, using multiple linear regressions adjusted for covariates. Levels were compared with those of 100 healthy controls. Results: Depressed mood was associated with higher levels of IL-4 (β = 0.167; p = 0.041). Psychic anxiety: lower IL-17 levels (β = –0.173; p = 0.039). Guilt feelings: lower IL-2 levels (β = −0.168; p = 0.041) Psychomotor retardation: higher IL-6 levels (β = 0.195; p = 0.017). Depressed patients’ TNF-α, INF-γ, and IL-4 levels were not significantly different from controls. Depressed patients’ IL-2, IL-6, IL-10, and IL-17 levels were higher than those of controls (p <0.001). Conclusion: Less severe MFs (depressed mood, psychic anxiety, and guilt feelings) were associated with an anti-inflammatory pattern (higher IL-4, lower IL-17 and lower IL-2, respectively). The presence of the most severe MF, psychomotor retardation, was associated with a higher pro-inflammatory response (higher IL-6).